The presence of extra chromosomes leads to genomic instability - Verena Passerini (Nature Portfolio, 2016)
One of the hallmarks of cancer cells is aneuploidy, however the molecular effects are poorly understood. Here the authors show that trisomic and tetrasomic cells display increased genomic instability and reduced levels of the helicase MCM2-7.